1987
DOI: 10.1063/1.98358
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen passivation of C acceptors in high-purity GaAs

Abstract: The effects of hydrogenation in high-purity p-type GaAs grown by molecular beam epitaxy and metalorganic chemical vapor deposition have been investigated by low-temperature photoluminescence and Hall-effect measurements. Before hydrogenation, photoluminescence measurements showed the dominant acceptor in the original samples was C, while after hydrogenation, the concentration of electrically active C acceptors was significantly reduced and the samples were highly resistive. These electrical and spectroscopic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…This layer covers the p-GaAs layer and prevents the surface recombination, which leads to a reduction in the extrinsic base current. (3) In the case of the InGaP-emitter, the surface recombination is significantly smaller compared to the AlGaAs-emitter. We thus conclude that the reduction in current gain is attributed to an increase in the I R , which is caused by defects-related recombination centers.…”
Section: Thermal Stability Of Carbon-doped P-gaasmentioning
confidence: 98%
See 1 more Smart Citation
“…This layer covers the p-GaAs layer and prevents the surface recombination, which leads to a reduction in the extrinsic base current. (3) In the case of the InGaP-emitter, the surface recombination is significantly smaller compared to the AlGaAs-emitter. We thus conclude that the reduction in current gain is attributed to an increase in the I R , which is caused by defects-related recombination centers.…”
Section: Thermal Stability Of Carbon-doped P-gaasmentioning
confidence: 98%
“…Carbon is commonly used as a p-type dopant for the base layer of the HBTs because of its high solubility, low diffusivity and no memory effect [1,2]. However, heavy carbon doping over 10 19 cm À3 by metal-organic chemical vapor deposition (MOCVD) incorporates large amounts of hydrogen atoms in the base layer [3,4]. The presence of hydrogen atoms affects the device performance [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al found that carbon acceptors in unintentionally carbon-doped epitaxial layers (N A ~ 10 x 5 cm-3) could be neutralized after exposure to a hydrogen plasma [72]. Clerjaud et al identified the hydrogen-stretching vibration of the CAs-H complex at 2635 cm -1 in the infrared (i.r.).…”
Section: The Hydrogen Passivation Of Carbonmentioning
confidence: 99%
“…Atomic-H has proved to be effective in passivating carrier concentration and improving material purity in III-V materials such as GaAs and InAs [6][7][8][9][10]. Furthermore, it has been found that atomic-H helps to promote an ideal layer-by-layer two-dimensional nucleation and step-flow growth mode on GaAs (100) substrate at low growth temperatures, thereby resulting in atomically flat surfaces [9].…”
Section: Introductionmentioning
confidence: 98%